Alcohol dependence, excessive drinking and deliberate self-harm: trends and patterns in Oxford, 1989-2002. - Haw, C; Hawton, K; Casey, D; Bale, E; Shepherd, A (2005)
BACKGROUND: Problems relating to alcohol use are very common among deliberate self-harm (DSH) patients, and alcohol abuse increases the risk of both DSH and suicide. In the UK, per capita consumption of alcohol has risen by 50% since 1970. The proportion of women (but not men) drinking in excess of government-recommended limits has also increased. We investigate trends, by gender and age group, in alcohol problems and usage among DSH patients. METHOD: Data collected by the Oxford Monitoring System for Attempted Suicide were used to examine trends in alcohol disorders and alcohol consumption shortly before, or at, the time of self-harm by patients aged 15 years or over between 1989 and 2002. RESULTS: Data were available on 10,414 patients who were involved in 17,511 episodes of DSH. The annual numbers of both male and female DSH patients rose progressively over the study period. Although rates of alcohol disorders and consumption remained higher in males than females, substantial increases were seen in females of all ages in rates of alcohol problems, excessive drinking and consumption of alcohol within 6 h of DSH and as part of the act of DSH. Rates for males largely remained unchanged. CONCLUSIONS: There has been a significant increase in excessive drinking and consumption of alcohol around the time of DSH by females but not males. These changes may relate to increases in the affordability and availability of alcohol and to social changes in drinking patterns. They have implications for services for DSH patients and may have an impact on future patterns of suicidal behaviour.